Bach and Mozart essays on the enigma of genius - Marshall, Robert L. 1939- (University of Rochester Press, 2019)
"The essays in this volume serve a single objective: to promote a deeper understanding of two of the greatest composers in history, as both supremely gifted creators and fellow human beings. The many fascinating topics include, among others, Bach's relationship to his sons, Martin Luther's importance in Bach's music and in his life, Bach's attitude toward the Jews, Mozart's wit, his portrayal in Amadeus, his evolving responses to Bach's influence, and the lessons of his unfinished works. Diverse interpretive approaches range from text criticism to style criticism and draw on Freudian and Schenkerian analysis, along with the ideas of Harold Bloom, Theodor Adorno, Edward Said, Maynard Solomon, Charles Rosen, and other challenging thinkers"--
Keywords: Bach, Johann Sebastian -- 1685-1750; Mozart, Wolfgang Amadeus -- 1756-1791; Luther, Martin -- 1483-1546; Komposition -- Musik; Bach, Johann Sebastian / 1685-1750 / Criticism and interpretation; Mozart, Wolfgang Amadeus / 1756-1791 / Criticism and interpretation; Music / 18th century / History and criticism; Aufsatzsammlung